GSTM1 Polymorphism, GSTT1 Polymorphism, and Cervical Cancer Risk: A Meta-Analysis. Issue 9 (1st November 2010) - Economopoulos, Konstantinos P.; Choussein, Souzana; Vlahos, Nikos F.; Sergentanis, Theodoros N.
Abstract : Introduction: A debate exists about whether glutathione S -transferase (GST) polymorphisms (GST mu-1 [GSTM1] null/present genotype and GST theta-1 [GSTT1] null/present genotype) confer additional risk for cervical cancer. This meta-analysis was aimed to examine the associations between the aforementioned polymorphisms and cervical cancer risk. Methods: Thirteen studies were eligible for GSTM1 (1616 cervical cancer cases and 1970 controls), and 12 studies were eligible for GSTT1 (1393 cases and 1766 controls). Pooled odds ratios (OR) were appropriately derived from fixed effects or random effects models. Separate analyses were conducted on Chinese and non-Chinese populations. Metaregression with publication year was also performed. Results: At the overall analysis, the GSTM1 null genotype was associated with increased cervical cancer risk (pooled OR = 1.272; 95% confidence interval [CI], 1.014-1.597, random effects). The association seemed confined to non-Chinese populations (pooled OR = 1.392; 95% CI, 1.003-1.932, random effects) given that the association was not significant in the subset of Chinese studies (pooled OR = 1.080; 95% CI, 0.870-1.340, fixed effects). On the other hand, at the overall analysis, the GSTT1 null genotype was not associated with increased cervical cancer risk (pooled OR = 1.301; 95% CI, 0.948-1.787, random effects). Similarly, no significant associations were detected in either non-Chinese or Chinese populations concerning the GSTT1 null genotype. Conclusions: The GSTM1 null genotype confers additional risk for cervical cancer in non-Chinese populations. The trend concerning GSTT1 has not reached significance.